Clinicopathologic features associated with efficacy and long‐term survival in metastatic melanoma patients treated with BRAF or combined BRAF and MEK inhibitors. Issue 21 (28th July 2015) - Menzies, Alexander M.; Wilmott, James S.; Drummond, Martin; Lo, Serigne; Lyle, Megan; Chan, Matthew M. K.; Thompson, John F.; Guminski, Alex; Carlino, Matteo S.; Scolyer, Richard A.; Kefford, Richard F.; Long, Georgina V.
<x xml:space="preserve">Abstract</x> BACKGROUND The degree of response and the duration of survival of patients treated with mitogen‐activated protein kinase (MAPK) inhibitors are highly variable. Whether baseline clinicopathologic factors can predict the clinical course with treatment is largely unknown. METHODS For 142 consecutive immunotherapy‐ and MAPK inhibitor–naive patients with BRAF‐mutant metastatic melanoma who were treated during clinical trials with BRAF inhibitors (n = 111) or a combination of dabrafenib and trametinib (n = 31), clinicopathologic factors were correlated with the response to MAPK inhibitors and survival. RESULTS The median follow‐up was 15.7 months (range, 0.6‐60.5 months). The 2‐, 3‐, and 4‐year overall survival (OS) rates were 43%, 24%, and 24%, respectively. A multivariate analysis demonstrated that the only clinicopathologic factors associated with longer progression‐free survival (PFS) and OS were female sex and a normal pretreatment serum lactate dehydrogenase (LDH) level. The BRAF V600E genotype and an absence of primary melanoma ulceration were also independently associated with longer PFS but not OS. The median OS was 23.5 months for patients with normal LDH levels and 7.3 months for those with elevated LDH levels (hazard ratio, 0.31; P < .001). Complete responders had the best survival, but disease progression still occurred in 2 of 7 patients. CONCLUSIONS Long‐term survival occurs for a minority of patients receiving MAPK inhibitor treatment alone. Sex, serum LDH, BRAF genotype, and primary melanoma ulceration status are independent factors associated with treatment outcomes. Patients with a complete response to treatment have the best survival, but relapses still occur. Cancer 2015;121:3826–3835. © 2015 American Cancer Society.